ANALYSIS OF RUNWAY AND TERMINAL CAPACITY OF THE POTENTIAL INCREASE OF THE NUMBER OF PASSENGER AT SANGGU AIRPORT (SOUTH BARITO) - Rahman Aulia Jauhari (INFO-TEKNIK, 2023)
An airport is a place for aircraft to operate both take-off and landing. Buntok City, South Barito Regency has Sanggu Airport as one of the main entrances for people's transportation routes. Sanggu Buntok Airport is a class III airport managed by UPBU. The airport currently has a runway length of 750 m x 23 m and a terminal building covering an area of 200 m2. In this study, an analysis of the runway service capacity was carried out to increase the number of passengers in the future, to meet the number of aircraft operations that can be served by the runway, and it is hoped that the results of this research can be used as evaluation material for the development of Sanggu Airport in the future. And for terminal capacity This study analysis the ground side of the airport, namely the service capacity of the passenger terminal towards the increase of passenger traffic in the future, to find out the number of passengers that can be handled by the terminal. Calculation of the passenger terminal capacity and the required terminal size is based on the SKEP/77/VI/2005. The calculation of maximum capacity is conducted by counting the number of available seats and the current size of the passenger waiting area continued with the calculation of the required terminal waiting area size after forecasting. From the results, it was found that the average saturation capacity of the runway for VFR conditions was 86 operations/hour and for IFR conditions the average saturation capacity was 58 operations/hour. After forecasting, the number of passengers in 2032 was 430 people with the number of flights being 215 flights and the number of passengers in 2037 being 714 people with the number of flights being 357 flights. Through the result of this analysis, it is known that the maximum waiting area capacity of the Sanggu Airport is 32 passengers, with a room size of 30,94 m2. Meanwhile, the maximum capacity of the arrival hall is 16 passengers, with an area size of 32,64 m2. After forecasting is conducted, the predicted traffic of passengers in 2032 is 860 passengers, and 1428 passengers in 2037. The numbers are based on the peak hour traffic of passengers in 2032, namely, 9 passengers/hour, which required a waiting area size of 14,52 m2 and the number of seats required is 9 seats. For the year 2037, the peak hour passenger traffic is forecasted to be 14 passengers/hour, therefore requiring a waiting area size of 22,59 m2 and the number of seats required is 14 seats. Based on the calculation, the standard required size for the arrival hall with a peak hour traffic of 9 passengers/hour in 2032, the required size of arriving hall is 18,56 m2. As for the year 2037 with the peak hour traffic of 14 passengers/hour, the required size of the arrival hall needed is 28,88 m2. When compared to the current size of the arrival hall of 32,64 m2 it can be concluded that the current arrival hall is sufficient to serve the airport until the year 2037. Keywords: airport, runway capacity, terminal capacity, forecasting